Implementation of A Fast ORB Keypoints Extraction Algorithm Based on Grid Division - Cao, Yuan; Lu, Jun; Zhang, Xu (International Journal of Computer Science and Information Technology, 2024)
Synchronous Localization and Mapping (SLAM) is a research hotspot in the field of mobile robots. However, visual SLAM faces a high computational burden in feature point extraction and other processes, thus requiring powerful computing and memory resources as support. This article proposes a fast ORB feature point extraction method based on grid partitioning to meet the requirements of fast and efficient feature point extraction in visual SLAM. This method can significantly reduce the time required for feature point extraction and also meet the requirement of uniform distribution of feature points in images in visual SLAM. Finally, in the experiment, the algorithm proposed in this paper was compared with the traditional ORB feature point extraction algorithm, verifying that this method has significant advantages in extraction speed.